Search for high-mass dilepton resonances in pp collisions at $\sqrt{s}=8$ TeV with the ATLAS detector - ATLAS collaboration (2881 authors) (2014)
The ATLAS detector at the Large Hadron Collider is used to search for high-mass resonances decaying to dielectron or dimuon final states. Results are presented from an analysis of proton-proton (pp) collisions at a center-of-mass energy of 8 TeV corresponding to an integrated luminosity of 20.3 fb-1 in the dielectron channel and 20.5 fb-1 in the dimuon channel. A narrow resonance with Standard Model Z couplings to fermions is excluded at 95% confidence level for masses less than 2.79 TeV in the dielectron channel, 2.53 TeV in the dimuon channel, and 2.90 TeV in the two channels combined. Limits on other model interpretations are also presented, including a grand-unification model based on the E6 gauge group, Z* bosons, Minimal Z' Models, a spin-2 graviton excitation from Randall-Sundrum models, quantum black holes and a Minimal Walking Technicolor model with a composite Higgs boson.